Management of the Forests of Jammu and Kashmir State - Kaul, P. N.; Fotidar, A. N. (Indian Forester, 1961)
In this paper a vast area, with varied climates, topography and forest-types has been gone over particularly in regard to the management of the more important forests. Management on scientific lines was introduced towards the close of the last century and the chief architect for this is undoubtedly, McDonnell who organised the department on the present day-lines in 1892. To begin with, the working plans drawn up by Mayes, Keshvanand, Fullar, Steane etc. prescribed a conservative working of more important species under a selection system with an exploitable girth of 7Â½. These plans individually covered vast tracts and the working under them was restricted to more easily accessible areas. With the switch over to the uniform system in the Himalayan conifer forests of the neighbouring states of the Punjab and the U.P., the working plans advocating this system for the important deodar-kail forests of the state were for the first time prepared by Sher Singh and Deans for the Lolah and Buniyar respectively. In these plans silviculture was more or less subordinated to theoretical concepts of management. Subsequent revisions, particularly by Khajuria for Lolab rectified this mistake but laid undue stress on keeping the yields conservative. In doing this the management got complicated and this is discussed. These plans and their first revisions prescribed fir on easy ground also to be worked under the uniform system. The yield regulation as followed in these plans is also discussed. The next phase of switching ovel' from a theoretical uniform to a conversion system starts, with Habib's plan for the Pir Panjal diviSion, in which, he also introduced Brandis' method of yield regulation in selection working circle. The short-comings and the errors in its application are also discussed. The current working plans in almost all cases, have followed the conversion system for the more important deodar-kail forests and the Indian selection system for fir and other conifers on steep ground. Management ofchir, willow, and bamboo is also briefly described.